International Labour Migration in the Middle East and Asia Issues of Inclusion and Exclusion - Lian, Kwen Fee.; Hosoda, Naomi; Ishii, Masako; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The discourse on migration outcomes in the West has largely been dominated by issues of integration, but it is more relevant to view immigration in non-Western societies in relation to practices of exclusion and inclusion. Exclusion refers to a situation in which individuals and groups are usually denied access to the goods, services, activities and resources associated with citizenship. However, this approach has been criticised in relation to gender issues, which are very relevant to the situation of migrants. The authors in this volume address this criticism. Furthermore, when framed within a North-South discourse, it may be potentially ethnocentric to assume that the experience of exclusion is cross-culturally uniform. Indeed, work on migration issues has invariably been conducted within such a discourse. The contributors go beyond this binary discourse of 'exclusion versus inclusion' which has dominated migration research. They examine the situation of migrants in the Middle East and Asia as one that encompasses both exclusion and inclusion, addressing related concepts of empowerment, ethnocracy, the feminisation of migration and gendered geographies of power, liberal constraint and multiculturalism, individual agency, migrant-friendly discourses, spaces of emancipation and spaces of insecurity. The book highlights current research in the Arab Gulf states, and examines multiculturalism in Asia more broadly. It will be of particular interest to students and researchers in international labour migration studies in the Middle East and Asia. .
Chapter 1 Introduction: Migrants in the Middle East and Asia -- Chapter 2 Ethnocracy in the Arab Gulf States: Oil Rent, Migrants, and Authoritarian Regimes -- Chapter 3 Empowerment of Migrant Domestic Workers: Muslim Filipinas in the UAE -- Chapter 4 Complexities of Inclusion and Exclusion amongst Intermarried Filipino Migrant Workers in the UAE -- Chapter 5 'This is Our Home, But We Cannot Stay Here Forever': Second Generation Asian Youth in Kuwait and the UAE -- Chapter 6 Promoting Diversity, Branding the State: Migrant-friendly Discourse in the UAE -- Chapter 7 Brunei Darussalam: Female Labour Force Participation and Foreign Domestic Workers -- Chapter 8 Space of Emancipation or Space of Insecurity: Gendered Dimensions in 'Nepal Town', South Korea -- Chapter 9 International Migration and the Politics of Multiculturalism in Japan, South Korea, and Singapore. .
Keywords: Emigration and immigration; Social legislation; Culture -- Study and teaching; Social policy; Human Migration; Labour Law/Social Law; Cultural Studies; Social Policy